2012
DOI: 10.1152/ajpheart.00617.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes of mesenteric arteries in pregnancy: a meta-analysis

Abstract: The vascular response to pregnancy has been frequently studied in mesenteric artery models by investigating endothelial cell (EC)- and smooth muscle cell (SMC)-dependent responses to mechanical (flow-mediated vasodilation, myogenic reactivity, and vascular compliance) and pharmacological stimuli (G protein-coupled receptor responses: Gq(EC), Gs(SMC), Gq(SMC)). It is unclear to what extent these pathways contribute to normal pregnancy-induced vasodilation across species, strains, and/or gestational age and at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
1
21
0
Order By: Relevance
“…Other studies have shown that G1 produces vasodilation similar to E2 in the carotid artery of a Sprague-Dawley rat of both genders (Broughton et al, 2010) and the mesenteric artery of a male SpragueDawley rat (Haas et al, 2009) and female mRen2.Lewis rat (Lindsey et al, 2011). These differences may be related to the rat strain, regional differences in ER distribution along the arterial tree (D'Angelo and Osol, 1993;van Drongelen et al, 2012), and hormonal changes during the estrous cycle, which could influence vascular function, and some of the studies in female rats did not report the stage of the estrous cycle or ] i were constructed in response to increasing concentrations (10 29 to 10 25 M) of E2 (all ERs), PPT (ERa agonist), DPN (ERb agonist), or G1 (GPR30 agonist) in microvessels pretreated with KCI (51 mM) alone (E and G) or KCI (24 mM) plus Bay K 8644 (F and H). Data points represent means 6 S.E.M., n = 4-12.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have shown that G1 produces vasodilation similar to E2 in the carotid artery of a Sprague-Dawley rat of both genders (Broughton et al, 2010) and the mesenteric artery of a male SpragueDawley rat (Haas et al, 2009) and female mRen2.Lewis rat (Lindsey et al, 2011). These differences may be related to the rat strain, regional differences in ER distribution along the arterial tree (D'Angelo and Osol, 1993;van Drongelen et al, 2012), and hormonal changes during the estrous cycle, which could influence vascular function, and some of the studies in female rats did not report the stage of the estrous cycle or ] i were constructed in response to increasing concentrations (10 29 to 10 25 M) of E2 (all ERs), PPT (ERa agonist), DPN (ERb agonist), or G1 (GPR30 agonist) in microvessels pretreated with KCI (51 mM) alone (E and G) or KCI (24 mM) plus Bay K 8644 (F and H). Data points represent means 6 S.E.M., n = 4-12.…”
Section: Discussionmentioning
confidence: 91%
“…One may question the validity of such extrapolations. A previous meta-analysis showed that in mesenteric arteries vascular adaptation to pregnancy is strongly dependent on species, strains and gestational ages [8]. This may also be the case for renal arteries.…”
Section: Introductionmentioning
confidence: 91%
“…or b. The mediating receptor complex involved [8]. Most studies have concentrated on agents that affect the G-protein coupled receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Such vasodilators include the kallikrein-kinin system, prostacyclin, nitric oxide and vascular-endothelial growth factor (VEGF). [48][49][50] In addition to the functional adaptation of the maternal cardiovascular system, structural changes also occur during pregnancy. This adaptive remodelling results in cardiac hypertrophy that enables the heart to cope with the increased demands of gestation.…”
Section: Risk Factorsmentioning
confidence: 99%